2010
DOI: 10.1136/emj.2009.086991
|View full text |Cite
|
Sign up to set email alerts
|

Recreational mountain biking injuries

Abstract: Mountain biking is increasing in popularity worldwide. The injury patterns associated with elite level and competitive mountain biking are known. This study analysed the incidence, spectrum and risk factors for injuries sustained during recreational mountain biking. The injury rate was 1.54 injuries per 1000 biker exposures. Men were more commonly injured than women, with those aged 30-39 years at highest risk. The commonest types of injury were wounding, skeletal fracture and musculoskeletal soft tissue injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 15 publications
4
42
0
Order By: Relevance
“…The age group most likely to be injured is 30-39 years. 2 We found that complex injuries to the shoulder girdle involving disruption of the four-bar linkage were more common in older cyclists. These injuries are more difficult to treat, although our group achieved good postoperative results.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…The age group most likely to be injured is 30-39 years. 2 We found that complex injuries to the shoulder girdle involving disruption of the four-bar linkage were more common in older cyclists. These injuries are more difficult to treat, although our group achieved good postoperative results.…”
Section: Resultsmentioning
confidence: 82%
“…2 We found that complex injuries to the Upper limb Clavicle 7 7 5 10 29 Scapula 0 1 2 2 5 Humerus 2 0 2 1 5 Radial head 2 0 3 6 11 Distal radius 1 3 4 6 14 Ulna 0 2 3 1 6 Metacarpals 1 2 2 7 12 Phalanges 2 1 3 4 10 Subtotal 15 16 24 37 shoulder girdle involving disruption of the four-bar linkage were more common in older cyclists.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…24 High-energy injury secondary to mountain biking and other cycling disciplines was no more common than in other sports. 23 In a 3-year study from North America, 28% of horse riding injuries resulted in bony injury, and approximately one-fifth of these fractures involved the skull, spine, or pelvis. 25 In a 10-year study of acute injuries in competitive European motocross riders, motocross was second only to motorcycle racing in terms of injury incidence; 25% of injuries were fractures, and one in 10 fractures involved the spine, pelvis, or hip.…”
mentioning
confidence: 99%